Immunomodulatory effect of bovine lactoferrin during SARS-CoV-2 infection - Silva, Andrea Marques Vieira da; Machado, Thiago Lazari; Nascimento, Ryann de Souza; Rodrigues, Miguel Pires Medeiros Diniz; Coelho, Felipe Soares; Tubarão, Luciana Neves; da Rosa, Lorenna Carvalho; Bayma, Camilla; Rocha, Vanessa Pimenta; Frederico, Ana Beatriz Teixeira; Silva, Jane; Cunha, Danielle Regina de Almeida de Brito e; et al. (Frontiers in Immunology, 2024)
Lactoferrin (Lf) is an important immunomodulator in infections caused by different agents. During SARS-CoV-2 infection, Lf can hinder or prevent virus access to the intracellular environment. Severe cases of COVID-19 are related to increased production of cytokines, accompanied by a weak type 1 interferon response. We investigated the influence of bovine lactoferrin (bLf) in the immune response during SARS-CoV-2 infection in vitro, and in vivo assays. Our results show a strong binding between bLf and TLR4/NF-kB in silico, as well as an increase in mRNA expression of these genes in peripheral blood mononuclear cells (PBMC) treated with bLf. Furthermore, the treatment increased TLR4/TLR9 mRNA expression in infected K18-hACE2 mice blood, indicating an activation of innate response. Our results show that when bLf was added, a reduction in the NK cell population was found, presenting a similar effect on PD-1 in TCD4 + and TCD8 + cells. In the culture supernatant of PBMC from healthy participants, bLf decreased IL-6 levels and increased CCL5 in COVID-19 participants. In addition, k18-hACE2 mice infected and treated with bLf presented an increase of serum proinflammatory markers (GM-CSF/IL-1b/IL-2), and upregulated mRNA expression of IL1B and IL6 in the lung tissue. Furthermore, bLf treatment was able to restore FTH1 levels in brain tissue. The data indicates that bLf can be part of a therapeutic strategy to promote the immunomodulation effect, leading to homeostasis during COVID-19.